(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
Today, among the important tasks in Ukraine, the problem of a careful attitude to one’s own health, as the highest social value, is becoming more and more active. Promoting the prevention of the most common negative habits involves the introduction of separate approaches and ways to stimulate a healthy lifestyle for applicants to higher education institutions. Strengthening and preserving health is a priority area of ​​​​the main legislative acts and regulatory documents on physical culture. As studies show, when applicants to LNTU answered the question: “How often do you smoke (how many cigarettes per day?)”, the vast majority of young people chose the option – I do not smoke. The largest percentage of applicants need to smoke up to 15 cigarettes per day. To answer the question: “How often do you drink alcoholic beverages?” several options were offered: once a week and more often; 2-3 times a month; several times a year; never. Among them, one option had to be chosen. The largest percentage of applicants to a technical university chose the answer option - several times a year (1st year: boys - 33.9%, girls - 41.1%). Among boys in the 2nd year of study, 25.0% each fell on the options - several times a year and never. 59.0% of girls from this stream indicate the option - 2-3 times a week. There is a small number of young people on the courses who never drink alcohol. Answering the questionnaire questions: "Do you use drugs?" and "Do you use toxic substances?" 3.5% of boys in the 1st year use drugs occasionally, and 1.7% - use toxic drugs occasionally. 100.0% of girls in the 1st and 2nd years have never used drugs or toxic substances. Thus, at Lutsk National Technical University, almost half of the respondents (40.0%) have negative habits, and the other half, who do not have them, are actively engaged in physical exercises. This once again emphasizes the fact that where physical activity is in the first place, it is not easy for negative habits to take root.